Antibody persistence and evidence of immune memory at 5 years following administration of the 9-valent HPV vaccine. Issue 37 (5th September 2017) - Guevara, Ana; Cabello, Robinson; Woelber, Linn; Moreira, Edson Duarte; Joura, Elmar; Reich, Olaf; Shields, Christine; Ellison, Misoo C.; Joshi, Amita; Luxembourg, Alain
Highlights: HPV antibody responses elicited by 9-valent HPV vaccine persist at least 5 years. A challenge vaccine dose induces an anamnestic response, indicative of immune memory. Immune memory is a hallmark of vaccines that offer long-lived protective immunity. Abstract: Background: The 9-valent HPV (9vHPV) vaccine was developed to prevent infection and disease related to 9 HPV types (HPV6/11/16/18/31/33/45/52/58) which cause approximately 90% of cervical cancers, HPV-related vulvar, vaginal and anal cancers, and genital warts worldwide. In a pivotal efficacy study, the 9vHPV vaccine prevented infection and disease due to the 9 vaccine types. Duration of protection remains to be determined. Vaccines that induce long-term protection are generally characterized by the generation of immune memory. The purpose of this report is to assess the persistence of HPV antibody response and existence of immune memory at 5 years post-vaccination. Methods: A subset of subjects (N = 150) who received 3 doses of 9vHPV vaccine at day 1, month 2 and month 6 in the pivotal efficacy study continued in a study extension and received a fourth dose of 9vHPV vaccine at month 60. Serum HPV antibody levels were measured pre-dose 4 and at 7 and 28 days post-dose 4 by competitive Luminex immunoassay. Adverse events were assessed using a vaccination report card. Results: HPV antibodies induced following the 3-dose series of 9vHPV vaccine in the base study persisted through month 60 with seropositivity rates ranging from 77.5% to 100%. Geometric mean titers at 1 week and 1 month post-dose 4 were 1.25–4.10 and 1.65–4.88-fold higher, respectively, than levels observed 1 month following the completion of the three-dose primary series. Seropositivity rates were >99% and 100% at 1 week and 1 month post-dose 4, respectively. The fourth dose of 9vHPV vaccine was generally well tolerated. Conclusions: A three-dose regimen of the 9vHPV vaccine induced persistent HPV antibody response through 5 years post-vaccination. Administration of a fourth dose resulted in a strong anamnestic response to all 9 vaccine types. These findings suggest that the efficacy of the 9vHPV vaccine will be long lasting. Clinical Trials.gov Identifier: NCT00543543 .